Challenges in implementing continuous support during childbirth in selected public hospitals in the North West Province of South Africa - Nobelungu S. Spencer; Antoinette du Preez; Catharina S. Minnie (AOSIS, 2018)
Background: According to a Cochrane review, continuous support during childbirth increases the mother's chances of a vaginal birth without identified adverse effects. However, this evidence-based practice is not universally implemented. The objective of the study was to identify challenges encountered in implementing continuous support during childbirth in public hospitals in the North West Province of South Africa.   Method: An explorative, descriptive and contextual qualitative approach was used. The data were collected during 2013 by conducting focus group interviews with 33 registered midwives who had worked in maternity units in three selected public hospitals in the North West Province for at least two years.   Results: Midwives identified challenges that negatively impacted the implementation of continuous support during childbirth at organisational and interpersonal levels. At the organisational level, challenges included human resources, policies and guidelines as well as the architectural outlay of the maternity units. The personal challenges related to communication and attitudes of nurses, patients and their families.   Conclusions: Organisational and personal challenges had a negative impact on the provision of continuous care during childbirth.